Multimode interference based fiber optic interferometer-simulation and implementation - Jeyasuriya, Joseph Kovil Pillai Jeminal (2016)
A sensor based on multimode interference (MMI) is presented and investigated for the measurement of refractive index. The RI sensor with a simple configuration of SMF-NCF-SMF is fabricated by sandwiching No Core fiber (NCF) of length 20mm with two single mode fibers (SMF). The sensing principle is based on the multi-mode interference wavelength shift in the NCF when the RI of surrounding liquid of fiber is changed. Numerical simulation is performed to verify the sensor performance. The RI sensor with the length of 20 mm NCF is fabricated and experimentally studied. The measurement of RI using this sensor is demonstrated with a sensitivity of 604.947nm/RIU in the RI range from 1.40 to 1.4338 and 133.647nm/RIU in the range from 1.33 to 1.393. The experimental results are well-matched with the simulation results.